INFLUENCE OF THE STYLE OF RELATIONSHIP OF THE TEENAGER-PARENT ON THE PROCESS OF THE SEX-ROLE IDENTITY - Avagimyan , R. A.; Melkumyan, A. G. (Modern Psychology, 2019)
Sexual identification of the teenager in the manifestations of a person’s social behavior and social roles constantly exists the trace of the sexual roles, which he/she has mastered in the family. The effect of the parents` relationships is high on the sexual socialization of the teenager, as well as on their own behavior, has a huge effect which can be positive and negative. It emerges as a result of parents` serious mistakes, it gives the teenager destructed norms of personal behavior, which the teenagers imitate and use not only within the framework of interfamilial relationships, but also within practical and interpersonal contact.
Keywords: teenager, sexual identification, styles of social and psychological influence, interpersonal relationships, parent- teenager relationship